Determining The Determinant Value Of The Matrix m x n Using Java - Rahmatullah, Saffa; Rizal, Yusmet (Journal of Mathematics UNP, 2024)
One of the important topics in algebraic mathematics is determining the determinant value of a matrix. In this case, the determinant of an m x n matrix or rectangular matrix is also called the Radic determinant. The calculation of the determinant of a rectangular matrix requires lengthy analysis and calculations if searched manually it will take a long time. The purpose of this research is to obtain a determinant algorithm of m x n matrix which is then implemented into a program and will be executed with Java programming language. This research is basic that uses literature review as its foundation and uses theoretical analysis related to the problem of programming algorithms and determining the determinant value of the m x n matrix using the Java language. The result of this research is a Java program to determine the determinant value of m x n matrix with conditions m is less than or equal to n.